Common Fixed Point Theorems of Quadruple Mappings Satisfying \(CLR\) Property in \(G_p\) Metric Spaces With Applications - Tiwari, Rakesh; Srivastava, S. K.; Thakur, Shashi (Communications in Mathematics and Applications, 2020)
The aim of this paper is to establish common fixed point theorems for quadruple of weakly compatible mappings satisfying a new type of common limit range property and involving almost altering distances in \(G_p\) metric space. Furthermore, we present an example to validate our main result. Further, we obtain some common fixed point theorems for mappings satisfying contractive conditions of integral type and for \(φ\)-contractive mappings.